2011
DOI: 10.1371/journal.pone.0018556
|View full text |Cite
|
Sign up to set email alerts
|

High Cleavage Efficiency of a 2A Peptide Derived from Porcine Teschovirus-1 in Human Cell Lines, Zebrafish and Mice

Abstract: When expression of more than one gene is required in cells, bicistronic or multicistronic expression vectors have been used. Among various strategies employed to construct bicistronic or multicistronic vectors, an internal ribosomal entry site (IRES) has been widely used. Due to the large size and difference in expression levels between genes before and after IRES, however, a new strategy was required to replace IRES. A self-cleaving 2A peptide could be a good candidate to replace IRES because of its small siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
1,100
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,194 publications
(1,154 citation statements)
references
References 18 publications
23
1,100
0
Order By: Relevance
“…Consistent with previous studies, we observed a high amount of protein degradation of the P2A* product , which correlated with the decrease in expression observed using confocal microscopy ( Figure S2). A barely detectable band that could correspond to a potential uncleaved product was sometimes observed using the a-mCherry antibody in T2A, E2A, and P2A lines ( Figure 1C), suggesting that, for these 2A viral peptides, a small residual fraction of noncleaved product may exist, as reported in some other models (Kim et al 2011). In sum, we found that each of the canonical F2A, T2A, E2A, and P2A viral peptides work efficiently in C. elegans.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Consistent with previous studies, we observed a high amount of protein degradation of the P2A* product , which correlated with the decrease in expression observed using confocal microscopy ( Figure S2). A barely detectable band that could correspond to a potential uncleaved product was sometimes observed using the a-mCherry antibody in T2A, E2A, and P2A lines ( Figure 1C), suggesting that, for these 2A viral peptides, a small residual fraction of noncleaved product may exist, as reported in some other models (Kim et al 2011). In sum, we found that each of the canonical F2A, T2A, E2A, and P2A viral peptides work efficiently in C. elegans.…”
Section: Resultssupporting
confidence: 79%
“…Because an uncleaved product can sometimes be detected, but not always, as already described in other species (Hasegawa et al 2007;Provost et al 2007;Gonzalez et al 2011;Kim et al 2011), we cannot exclude that, in rare cases, low amounts of an uncleaved product could be associated with a dominant negative activity. It should be noted that this has never been described, while the multi-subunit T-cell receptor, or cocktails of pluripotency factors, for example, have been delivered to cells with no adverse effects (Szymczak et al 2004;Carey et al 2009).…”
Section: A Peptides Can Simultaneously Deliver Five Distinct Functiomentioning
confidence: 85%
See 1 more Smart Citation
“…To determine the feasibility of our KI approach, the GFP coding region was fused in frame with the selection marker Neomycine phosphotransferase II (NPTII) using the self-cleaving peptide 2A (Kim et al, 2011) as a bridge (Supplemental Figure 4). The translation start codon "ATG" was removed from this fusion cassette in order to inhibit any undesired translation caused by random insertion of the T-DNA into the rice genome.…”
Section: Accepted Manuscript M Amentioning
confidence: 99%
“…The use of 2A variants can avoid potential intramolecular homologous recombination of polycistrons, and allows for the expression of multiple genes (up to five genes). There are four widely used 2A sequences, which are derived from the foot-and-mouth disease virus (F2A), porcine teschovirus-1 (P2A), Thoseaasigna virus (T2A), and equine rhinitis A virus (E2A), with P2A as the most effective one [98]. 2A is active in all eukaryotic cells [99], but not in prokaryotes [100].…”
Section: A Peptides and Ires For Construction Of Polycistron Vectorsmentioning
confidence: 99%